Quinolone-3-diarylethers: a new class of antimalarial drug. - Nilsen, A; LaCrue, A; White, K; Forquer, I; Cross, R; Marfurt, J; Mather, M; Delves, M; Shackleford, D; Saenz, F; Morrisey, J; Steuten, J; et al. (American Association for the Advancement of Science, 2013)
The goal for developing new antimalarial drugs is to find a molecule that can target multiple stages of the parasite's life cycle, thus impacting prevention, treatment, and transmission of the disease. The 4(1H)-quinolone-3-diarylethers are selective potent inhibitors of the parasite's mitochondrial cytochrome bc1 complex. These compounds are highly active against the human malaria parasites Plasmodium falciparum and Plasmodium vivax. They target both the liver and blood stages of the parasite as well as the forms that are crucial for disease transmission, that is, the gametocytes, the zygote, the ookinete, and the oocyst. Selected as a preclinical candidate, ELQ-300 has good oral bioavailability at efficacious doses in mice, is metabolically stable, and is highly active in blocking transmission in rodent models of malaria. Given its predicted low dose in patients and its predicted long half-life, ELQ-300 has potential as a new drug for the treatment, prevention, and, ultimately, eradication of human malaria.